Plurality in Legislative Media: An Analysis of the Chamber News Agency - Patrício, Edgard; Viana, Leidyanne (Brazilian journalism research, 2016)
For this paper, we used content analysis for the analysis of 115 news reports to determine if there is plurality in the Chamber News Agency news reports. The decision to choose plurality was based on the fact that it is a fundamental requisite for promoting public interest in journalism. The conclusion was drawn that there is currently no plurality due to predominant parliamentary sources taking up the majority of the space, leaving minimal space for the participation of society. Moreover, the only sources the Agency has are social agents authorized by the Chamber of Deputies.